A tribute to Professor Dr Kai A. I. Zhang: pioneering advances in metal-free polymeric photocatalysis - Bayarkhuu, Bolormaa; Kumar, Sunil; Byun, Jeehye (John Wiley & Sons Inc., 2026)
Polymeric photocatalysts have emerged as promising alternatives to traditional metal-based catalysts due to their tunable properties, low cost and environmental friendliness. This review highlights the significant contributions of Professor Dr Kai A. I. Zhang in advancing the field of polymeric photocatalysis. By leveraging the structural versatility of polymers, Professor Zhang's work has developed innovative strategies to enhance light absorption, charge separation and catalytic activity. The review delves into the fundamental principles underlying polymeric photocatalysis, including exciton generation, charge carrier dynamics and surface reactions. It further explores the design considerations for optimizing polymer structures to achieve efficient photocatalytic performance. Key advancements in the synthesis and characterization of polymeric photocatalysts are discussed, along with their applications in various chemical transformations. Professor Zhang's pioneering work has opened up new avenues for the development of sustainable and efficient photocatalytic systems, driving the transition towards a greener future. © 2025 The Author(s). Polymer International published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.